2021
DOI: 10.1039/d1gc02547c
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic cross-dehydrogenative couplings of N-heteroarenes with toluene derivatives at room temperature

Abstract: A mild aerobic cross-dehydrogenative coupling between N-heteroarenes and benzylic C(sp3)-H bond has been achieved through the visible-light-induced photocatalysis. This approach provides a sustainable alternative to Minisci benzylation reactions with readily...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Green development has always been an eternal topic in the field of chemistry. The radical reactions, a class of new and developing reactions, have received extensive attention of chemists because of their mild conditions, rapid reactions, and diverse reaction forms. , Combining the requirements of green development and our interest in radical reactions, we develop a transition-metal-free alkylation/ipso-cyclization of activated alkynes with 4-alkyl-1,4-dihydropyridines for the preparation of 3-alkylated aza - and oxa -spiro­[4,5]-trienones, in which H 2 O provides an oxygen atom for the construction of the newly generated carbonyl group (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Green development has always been an eternal topic in the field of chemistry. The radical reactions, a class of new and developing reactions, have received extensive attention of chemists because of their mild conditions, rapid reactions, and diverse reaction forms. , Combining the requirements of green development and our interest in radical reactions, we develop a transition-metal-free alkylation/ipso-cyclization of activated alkynes with 4-alkyl-1,4-dihydropyridines for the preparation of 3-alkylated aza - and oxa -spiro­[4,5]-trienones, in which H 2 O provides an oxygen atom for the construction of the newly generated carbonyl group (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above described mechanism studies and previous reports, 11,17,23 a detailed description of our proposed mechanism cycle for the direct arylation of benzylic C(sp) 3 –H bonds through photoredox HAT–nickel dual catalysis is shown in Scheme 3. The Ni II aryl bromide intermediate C was furnished via the oxidative addition of Ni(0) complex B to aryl bromide 2 .…”
Section: Resultsmentioning
confidence: 99%
“…8 However, in our previous report, we found that a bromine radical could activate the benzylic C–H bonds. 11 On this basis, we examined the direct arylation in the presence of 4-bromobenzonitrile ( 1a ), 1-methoxy-4-methylbenzene ( 2a , 10 equiv. ), [Ir(dF(CF 3 )ppy) 2 (dtbpy)]PF 6 ( PC1 ), NH 4 Br, Ni(acac) 2 , dtbbpy ( L1 ) and K 2 HPO 4 in acetone, which delivered 1,1-diaryl alkanes 3a in 92% yield (Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-dehydrogenative coupling (CDC) reaction between two readily available chemical entities has emerged as an important and straightforward synthetic strategy for C–N bond formation, whereby the only byproduct is H 2 formally. 35 On the other hand, photocatalytic organic synthesis is a continuous hot topic using visible light as green energy under environmentally friendly conditions. 36,37 In particular, visible light catalyzed/promoted cross-dehydrogenative coupling reactions represent a powerful C–N bond formation platform to produce various nitrogen-containing fine chemicals.…”
Section: Introductionmentioning
confidence: 99%